Compact microwave six-port vector voltmeters for ultra-wideband applications - Bialkowski, M. E. (Institute Electrical Electronics Engineers Inc, 2007)
This paper presents the design of two compact fully integrated six-port devices, which, from scalar power measurements, are capable of determining the ratio of two complex voltages or two complex wave amplitudes over an ultra-wide frequency band of 3.1-10.6 GHz. These vector voltmeters are formed by multilayer microstrip/slot couplers and power dividers that are assembled without using wire vias or crossovers. An ultra-wideband operation of these fully integrated six-port voltmeters is confirmed by full electromagnetic simulations and measurements.